2020
DOI: 10.1007/s00127-020-01959-w
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood internalizing problems, externalizing problems and their co-occurrence and (mal)adaptive functioning in emerging adulthood: a 16-year follow-up study

Abstract: Purpose A vast amount of studies suggest that internalizing or externalizing problems are related to individual functioning, and often co-occur. Yet, a focus on their additive and interactive effects is scarce. Furthermore, most research has focused on a limited number of developmental domains and mostly on maladaptive functioning. Therefore, the current prospective study examined whether early childhood (ages 4–8) internalizing and externalizing problems and their interaction were related to a broad range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 66 publications
2
38
0
1
Order By: Relevance
“…The findings in relation to mental health are to be expected, with much literature highlighting the continuity of early problems with socio-emotional functioning and later onset of mental health conditions [ 69 ]. The evidence is stronger for early externalising behaviours and their impact on both internalising and externalising behaviours in adolescence, and this is supported by wider literature [ 70 , 71 ]. A finding of this review is that there is more evidence that behaviours such as aggression and hyperactivity pose a risk to future mental health than anxious/withdrawn behaviour, particularly for externalising outcomes.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The findings in relation to mental health are to be expected, with much literature highlighting the continuity of early problems with socio-emotional functioning and later onset of mental health conditions [ 69 ]. The evidence is stronger for early externalising behaviours and their impact on both internalising and externalising behaviours in adolescence, and this is supported by wider literature [ 70 , 71 ]. A finding of this review is that there is more evidence that behaviours such as aggression and hyperactivity pose a risk to future mental health than anxious/withdrawn behaviour, particularly for externalising outcomes.…”
Section: Discussionsupporting
confidence: 61%
“…A finding of this review is that there is more evidence that behaviours such as aggression and hyperactivity pose a risk to future mental health than anxious/withdrawn behaviour, particularly for externalising outcomes. This finding should be interpreted cautiously because it may be that early internalising behaviours, compared to externalising, are more likely to resolve by early adolescence [ 72 ], or it may be that internalising is harder to identify, whereas externalising behaviours are more obvious and easier for parents and teachers to report, which could lead to less associations being observed for internalising behaviours and consequently less associations found [ 39 , 70 ]. The finding that emotional wellbeing was more closely associated with later internalising may be because emotional stability promotes regulation and mood stability leading to less internalising [ 73 ], but other studies have found that emotional wellbeing (in terms of regulation skills) is associated quite strongly with both internalising and externalising, but particularly so for internalising after the early years [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions have been associated with serious negative outcomes for youth including lower educational achievement, illicit substance use, risky sexual behavior, delinquent behavior, and increased suicide risk [ 6 ]. Beyond this, these internalizing symptoms frequently persist into adulthood and are associated with an increased risk of co-occurring disorders, criminal involvement, lower wage earnings, and early mortality [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Internalizing problems are related to inappropriate or maladjusted control of emotions and cognitions. These are defined by the presence of anxiety/depression symptoms, withdrawn, or somatic complaints (Achenbach, 1966 , 1991 ; Arslan et al, 2020 ). Internalizing difficulties are mainly predictive of victimization behaviors, particularly in girls (Casper & Card, 2016 ; Cosma et al, 2018 ; Zych et al, 2020a ).…”
Section: Social Skills Behavior Problems and Bullying Engagementmentioning
confidence: 99%
“…In contrast, externalizing problems refer to behaviors that reflect a negative impact on the environment (Campbell et al, 2000; Eisenberg et al, 2001). Often, externalizing difficulties are characterized by the presence of disruptive and/or aggressive behaviors (Achenbach, 1966 , 1991 ; Arslan et al, 2020 ). Externalizing problems are also strongly connected to bullying engagement (Jenkins & Nickerson, 2017 ).…”
Section: Social Skills Behavior Problems and Bullying Engagementmentioning
confidence: 99%